DETERMINANTS OF FIRM VALUE: PROPERTY AND REAL ESTATE COMPANIES (IDX) - FERNANDEZ, JESSLYN HO; PUSVIKASARI, NILA (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
The fundamental of this research is to obtain empirical evidence regarding the influence of Return on Asset (ROA), Debt to Equity Ratio (DER), Current Ratio (CR), Sales Growth, and Firm Size as independent variables on Firm Value as dependent variable in companies listed in Indonesia Stock Exchange (IDX). The population for this research is properties and real estate companies listed in Indonesia Stock Exchange (IDX) over the eight years period 2015-2022. There are 224 sample data that selected using purposive sampling method. The sample are tested and analyzed using multiple regression model.Based on the results of this study using Eviews 10, the result findings can be summarized as follows. Return on asset (ROA), sales growth, and firm size has effect firm value. While other variables such as Debt to Equity Ratio (DER) and Current Ratio (CR) has no effect firm value.